Gambaran Peran Keluarga tentang Pencegahan Ulkus Dekubitus pada Pasien Stroke dengan Gangguan Mobilitas Fisik - Dodik Arso Wibowo; Bagaswara Dwi Saputra (STIKES Karya Husada Kediri, 2019)
Decubitus ulcer is a disease caused by the patient's position does not change for more than 6 hours. Families with one family member suffering from a stroke need a family role about preventing the occurrence of ulcer ulcers as soon as possible. Stroke has physical symptoms of weakness in extremities that result in impaired physical mobility. This can cause complications in patients, if patients do not get good care by the family. This study aims to determine the role of the family regarding prevention of pressure sores in stroke patients with impaired physical mobilization in the UPTD Working Area of ​​Adan-Adan Health Center, Kediri Regency. The study was conducted on 30 March-30 June 2019. The design of this study used descriptive. The study population was 69 respondents, a large sample of 15 respondents who met the research criteria using purposive sampling technique, the research instrument in the form of a questionnaire, the data were analyzed by percentage and interpreted quantitatively. The results of the study obtained from 15 respondents, most of the respondents were 8 respondents (53%) had sufficient roles, almost half of the respondents were 4 respondents (27%) had a good role and a small number of respondents were 3 respondents (20%) had a role lack of prevention of pressure sores in stroke patients with impaired physical mobility. This is caused by several factors, namely age, work, education, and information obtained. Health workers are expected to provide counseling to families who have family members who suffer from stroke to further enhance their role and management in an effort to prevent pressure ulcers in stroke patients with impaired physical mobility in a good and correct manner.